Phenotype and genotype analyses in seven families with dentinogenesis imperfecta or dentin dysplasia. (24th January 2017) - Li, F; Liu, Y; Liu, H; Yang, J; Zhang, F; Feng, H
Abstract : Objective: Hereditary dentin defects can be categorised into two classes according to their clinical manifestations: dentinogenesis imperfecta (DGI), which includes three types (DGI‐I, DGI‐II and DGI‐III), and dentin dysplasia (DD), which includes two types (DD‐I and DD‐II). This study investigated the phenotypic characteristics and genetic causes of hereditary dentin defects in seven Chinese families. Materials and methods: Seven families affected with DGI‐II, DGI‐III or DD‐II were enrolled. Clinical examinations were performed to determine the phenotypic characteristics, and DNA samples were collected for Sanger sequencing. Results: Clinical diagnoses revealed DGI‐II in five families, DGI‐III in one family and DD‐II in one family. Variants of the dentin sialophosphoprotein ( DSPP ) gene were found in six of the seven families. Of these, c.52G>T was identified in two families. Each of the remaining four families had a different variant: c.2684delG, c.52‐2A>G, c.1874‐1877delACAG and c.3509‐3521del13bp; the last three variants were novel. Conclusions: This is the first study to analyse all three important types of hereditary dentin defect and include comprehensive genetic analyses of both dentin sialoprotein and dentin phosphoprotein in Chinese families. This study expands the spectrum of DSPP variants, highlighting their associated phenotypic continuum.